Randomization, bootstrap and Monte Carlo methods in biology - Manly Bryan F J (Boca Raton Chapman & Hall, 2007)
This book focuses on three related areas in computational statistics: randomization, bootstrapping, and Monte Carlo methods of inference. The author emphasizes the sampling approach within randomization testing and confidence intervals. Similar to random
Keywords: Biometry; Monte Carlo method; Sampling (Statistics)